Complicaciones de pacientes con pancreatitis aguda severa - Bryan Paul, Costales Montalvo (2020)
Severe acute pancreatitis is described as a current health problem, due to the risk in patients due to the multiple complications that can develop, and therefore, increasing the risk of mortality, as well as being a reason for admission to intensive care units, with all that goes with it. This research has the purpose of describing the behavior and management of severe acute pancreatitis, its complications are these: pre-surgical, trans-surgical or post-surgical; In addition, results are displayed described in the current literature on the stay in intensive care units and data about life´s quality after discharge that is offered to patients who went through this condition; through a documentary bibliographic review, for the analysis of 81 scientific articles, published in the languages: English, Spanish and Portuguese; respecting the criteria of information, exhaustiveness and topicality; in addition to respect for the bioethical principles determined for such investigative work. The results of this research shows the need to knowledge about the natural course of acute pancreatitis, it when classified as severe, compromises the patient with many complications from the pathology and from procedures performed to treat, since with it, we will avoid an increase in the morbidity and mortality that surrounds this condition, giving the patient adequate management therefore, improving their prognosis, to subsequently contribute to a satisfactory quality of life based on the necessary medical actions.